Peranan Politik Hukum Dalam Penyelenggaraan Pelayanan Publik Untuk Mewujudkan Good Governance - Ratu Mawar Kartika (Collegium Studiosum Journal, 2022)
When the law acts as a tool of social engineering (law as a tool of social engineering) inevitably places the rule of law in a very important position in regulating people's lives. Public policy is often understood as an instrument used by the government to solve technocratic public problems. Departing from the above background, the problem to be revealed is the extent to which the success of legal politics in the implementation of public services in Indonesia in realizing good governance. Based on the discussion that has been described above, it can be concluded that the role of legal politics is very much needed in the implementation of excellent public services in order to achieve good governance.